(untitled) (Research, Society and Development, 2021)
The current globalization process has accelerated pari passu the movement of people and the consumption process, breaking the usual social and geographic lines. The rise of technology is designing a new economy, to the detriment of old applied economic practices, forcing people to change their ways of behaving like consumers. Shaping a new moment in terms of dimension, speed, flow, and direction, Contemporary world history records an unparalleled economic transformation of wealth in progress. We had already foreseen this change, but its arrival ended up impacting us, and in its wake, there are more unforeseen events than certainties, and people around the world feel all this up close. In the composition of this scenario, it is essential to mention the embarrassments caused by the pandemic caused by the new coronavirus, which added even more instability to the world’s economic and structural bases. On the other hand, gradually, people aim for a more reasonable quality of life and consequent consumption. All this hangs over consumer behavior, which is the central object of our approach. Therefore, this article aims to identify consumer behavior in the act of shopping. Through the registration of motivational factors, the conditioning sources, attitudes and phases that make up the decision-making process of the consumer, adopting the bibliographic research method, opting for authors with propositions in the segment, what is most meritorious and of reference currently in the environment theoretical on the subject.